Application of K-Medoids Clustering to Increase the 2020 Family Planning Program in Sleman Regency - Febriyanti, Syintya; Nugraha, Jaka (Enthusiastic : International Journal of Applied Statistics and Data Science, 2022)
Indonesia is a country with a large population. Based on the results of the 2020 census, Indonesia's population ranks fourth in the world. The Indonesian government has made a policy to reduce population growth, namely the Family Planning Program or Keluarga Berencana (KB). One of the areas that did not escape the target was the DIY. Based on BKKBN DIY data, there is a significant difference between the number of active KB participants and the number of couples of childbearing ages, the number of KB equipment and the number of KB health facilities that exist between sub-districts in Sleman Regency. Then the sub-district classification is carried out based on the 2020 KB data in Sleman Regency using the K-Medoids Clustering method. This study aims to see the sub-district grouping used as a reference by the government in increasing active KB participants in the community to overcome the population in Yogyakarta, primarily focusing on Sleman. The categories in each cluster, namely Cluster 1, which consists of 6 sub-districts, have a high level of KB active participants, couples of reproductive ages, KB equipment, and KB health facilities. Then Cluster 2, which consists of 6 sub-districts, has a medium level of KB active participants, couples of reproductive ages, KB equipment, and KB health facilities. While Cluster 3 consists of 5 sub-districts, where KB active participants, teams of reproductive age, KB equipment, and KB health facilities are low level.